2022
DOI: 10.2147/ijgm.s373191
|View full text |Cite
|
Sign up to set email alerts
|

Resilience as a Source of Easement to Health-Related Worries in Women at Increased Risk for Breast or Ovarian Cancer During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has affected individuals' and society's physical and psychological well-being. The study was conducted in order to assess the predictors for health-related worries during the COVID-19 pandemic in vulnerable populations. Patients and Methods: A cross-sectional web-based survey of women who had a higher risk of developing breast cancer (BC) or ovarian cancer (OC) was conducted, regardless of whether they had experienced an active malignant disease during the pandemic. A self-reported questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Resilience is a transdiagnostic protector against mental disorders and a decreasing quality of life among individuals faced with diverse adversities [ 72 , 73 , 74 , 75 , 76 ]. Recently it was revealed that resilience helped alleviate health-related worries in women with an increased risk for breast or ovarian cancer [ 77 ]. Resilience is also an important source of healthy adaptation for people despite encountering difficulties [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is a transdiagnostic protector against mental disorders and a decreasing quality of life among individuals faced with diverse adversities [ 72 , 73 , 74 , 75 , 76 ]. Recently it was revealed that resilience helped alleviate health-related worries in women with an increased risk for breast or ovarian cancer [ 77 ]. Resilience is also an important source of healthy adaptation for people despite encountering difficulties [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resilience in breast cancer patients is both a state and a trait, as demonstrated by a study investigating resilience’s role in these patients ( 48 ). In the context of the COVID-19 pandemic, it was found that breast cancer patients with higher levels of resilience had fewer concerns about tumor progression due to COVID-19 infection ( 49 ). Resilience, therefore, plays a crucial role in the quality of life of breast cancer patients and their ability to cope with diagnosis, treatment, and recovery.…”
Section: Introductionmentioning
confidence: 99%